Surface-attached molecular beacons light the way for DNA sequencing - Palecek, Emil (Trends in biotechnology, 2004)
Rapid testing of DNA and RNA nucleotide sequences is required for various research protocols including wide-scale genetic testing, diagnostics, fast detection of biological warfare agents, environmental testing and forensic medicine. At present many laboratories are interested in research and development of an inexpensive, easy-to-use, fast-response device for this purpose. Various methods based on acoustic, electronic and optical detection of the DNA hybridization event have been reported.
Keywords: optika a fotonika; DNA Probes; Fluorescent Dyes; fluorescenční spektrometrie; Sequence Analysis, DNA; biosenzitivní techniky; sekvenční analýza DNA; Electrochemistry; akustika; Optics and Photonics; Acoustics; Biosensing Techniques; elektrochemie; barvení a značení; fluorescenční barviva; DNA; DNA sondy; Staining and Labeling; Spectrometry, Fluorescence